1993
DOI: 10.1002/ccd.1810290204
|View full text |Cite
|
Sign up to set email alerts
|

Management of typical and dysplastic pulmonic stenosis, uncomplicated or associated with complex intracardiac defects, in juveniles and adults: Use of percutaneous balloon pulmonary valvuloplasty with eight‐month hemodynamic follow‐up

Abstract: To alleviate large fixed right ventricular (RV) outflow gradients, percutaneous balloon dilatation of pulmonic stenosis (PS) was performed in 38 patients with mean age of 14 +/- 14 years (median: 9 years, age range: 9 months to 63 years). There were 21 males and 17 females. Thirty-four patients had typical PS (5 of them also having other complex congenital cardiac anomalies, while 13 additional patients had a patent foramen ovale); 2 further subjects had subpulmonic, and 2 dysplastic pulmonary valvular obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The mobility of a dysplastic pulmonary valve is so impaired that surgery is most often the preferred treatment of choice. However, some patients with dysplastic valves may still do well with pulmonary catheter balloon valvuloplasty [5]. Chen et al [4] reported on their results using the Inoue technique in adults and adolescents.…”
Section: Valvuloplasty Techniquesmentioning
confidence: 97%
See 2 more Smart Citations
“…The mobility of a dysplastic pulmonary valve is so impaired that surgery is most often the preferred treatment of choice. However, some patients with dysplastic valves may still do well with pulmonary catheter balloon valvuloplasty [5]. Chen et al [4] reported on their results using the Inoue technique in adults and adolescents.…”
Section: Valvuloplasty Techniquesmentioning
confidence: 97%
“…Unique to pulmonic stenosis is the situation of the dysplastic valve associated with complex intracardiac defects. David et al [5] reported on the results of percutaneous balloon dilatation for pulmonic stenosis in 38 patients ranging from 9 months to 63 years in age. Thirty-four patients had typical pulmonary stenosis, with 5 having complex congenital cardiac anomalies.…”
Section: Complications After Pulmonic Valvuloplastymentioning
confidence: 98%
See 1 more Smart Citation
“…42 PBV is the procedure of choice for children and adults with severe or symptomatic PS and carries a low risk of morbidity, mortality, and restenosis. 14,[43][44][45][46][47][48] However, a high frequency of PR has been reported; after PBV, 57% of children had moderate or severe PR at the last follow-up. 49 These data emphasize the need for lifelong follow-up after PBV.…”
Section: Bruce and Connolly A Contemporary Review Of Right-sided Valvmentioning
confidence: 99%